The Effect of Financial Literacy, Financial Attitudes, and Financial Planning on Student Financial Behavior in West Java - Barus, Irwan Irawadi; Chandra, Johnny; Fitriani, Heny; Nindiasari, Avininda Dewi; Sudarmanto, Eko (Westscience Press, 2025)
This study examines the impact of financial literacy, financial attitudes, and financial planning on the financial behavior of students in West Java. Using a quantitative approach, data were collected from 170 student respondents through questionnaires with a 5-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results show that financial attitudes, financial literacy, and financial planning have positive and significant effects on financial behavior. Among the three variables, financial attitudes have the strongest influence, followed by financial literacy and financial planning. The model explains 81.5% of the variance in financial behavior, indicating strong predictive power. These findings highlight the importance of fostering positive financial attitudes, enhancing financial knowledge, and encouraging structured financial planning to promote responsible financial behavior among students. The study contributes to the growing body of literature in behavioral finance and provides practical insights for educators and policymakers in designing effective financial education programs.